Policing the internal Schengen borders – managing the double bind between free movement and migration control - Casella Colombeau, Sara (Policing and society, 2017)
Analyses of security practices at borders have focused on the dematerialisation and de-territorialisation of control of individuals’ mobility. This paper explores the nature of the control the state still exercises over individuals’ mobility at national borders. It focuses on a border that is supposed to have been opened, between France and Italy, inside the Schengen Area. It is based on analysis of the practices, representations and organisation of French border police officers, beginning with the legal and organisational transformations due to implementation of the Schengen Convention at the France-Italy border. It then turns to the study of border police officers’ targeting practices, using Heyman's notion of a ‘plausible story’. Finally, it assesses the influence of deportation practices on the territoriality of the control of individuals’ mobility, as well as its effects on targeting practices. These borders are at the core of the interaction between the construction of a new, European political centre, and the affirmation of an older one, the national, political centre. This paper demonstrates that border police officers are in charge of dealing with the tension, a double bind of sorts, emerging from this interaction. National, internal borders are still a site in which the state manages individuals’ mobility.